The Interaction of Personal and Communal Identities in Literature - Krasnovas, Aleksandras (Respectus Philologicus, 2013)
This article is part of a larger group project designed to examine the memories and identities of multicultural Lithuanian border communities, and focuses on the town of Vilkyškis and its environs. The aim of the article is to investigate how problems of personal and communal identity are expressed in the literature of writers from the region. The study examines the novels of I. Simonaitytė and A. Petraitytė, prose writers whose works describe life in Klaipėda district and Lithuania Minor. The concepts of individual and collective identity, as described by the hermeneuticist Heidegger and the cultural sociologist Giddens, form the basis of the explanation of the theoretical aspects of personal and communal identities and their interactions. Pesonal identity is formed by two types of experience: direct sensory experience, and so-called mediated (received through intermediaries) experience. The article analyzes the novels of Simonaitytė and Petraitytė to determine how communal traditions and important aspects of national identity are passed down the generations, and questions why some traditions are absorbed naturally, others only with effort, while still others are rejected outright. The “nuclear family” has the greatest influence on personal identity, more so than the “extended family.” Other influences include the local village or town community, while the “extended community” affects public life.